209k views
5 votes
Write the quadratic question f(x)=3x^2-24x+49 in the form of f(x)= a(x-h)^2+k

User Starpause
by
6.2k points

1 Answer

6 votes

Answer:

f(x) = 3(x -4)^2 +1

Explanation:

Usually you start by factoring the leading coefficient from the first two terms:

f(x) = 3(x^2 -8x) +49

Now, you add the square of half the x-coefficient inside parentheses, and subtract the same quantity outside.

f(x) = 3(x^2 -8x +(-4)^2) -3(-4)^2 +49

= 3(x -4)^2 -48 +49

f(x) = 3(x -4)^2 +1 . . . . . . . . the vertex form you desire

User Greg Biles
by
6.1k points